Efektifitas Lembaga Penjamin Simpanan (LPS) Dalam Menjalankan Fungsinya Di Indonesia - Dian Kartika (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Meto, 2020)
Based on Law Number 24 of 2004 concerning the Deposit Insurance Corporation (LPS). LPS is an independent institution whose function is to guarantee the deposits of depositing customers and to actively participate in maintaining the stability of the banking system in accordance with their authority. The enactment of this act indicates that the importance of customer confidence in the banking industry is very influential on the economy in Indonesia to maintain the balance of progress and national economic unity. The purpose of this research is to find out and understand the effectiveness of LPS in carrying out its function as an institution that guarantees depositors' savings and actively participates in maintaining the banking system in accordance with their authority. The research method used by the researcher is normative legal research by collecting data in library research. The results of this study are the LPS always carry out a process of transformation from year to year to improve the effectiveness of its functions in carrying out bank guarantees and resolutions, especially the ability in the resolution of medium and large scale commercial banks. However, LPS also needs to tighten supervision of BPRs not only to focus on commercial banks so that BPRs will not be liquidated anymore.